2017
DOI: 10.1111/pbi.12715
|View full text |Cite
|
Sign up to set email alerts
|

Activation of secondary cell wall biosynthesis by miR319‐targeted TCP4 transcription factor

Abstract: SummaryThe overexpression of miR319 in plants results in delayed senescence, and high levels of miR319‐targeted TCP4 transcription factor cause premature onset of this process. However, the underlying mechanisms of this pathway remain elusive. Here, we found that miR319 overexpression results in a decrease in TCP4 abundance and secondary cell wall formation in the stem. Conversely, constitutive expression of miR319‐resistant TCP4 promotes secondary cell wall formation, indicating that miR319‐mediated TCP4 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 43 publications
(68 reference statements)
2
68
0
Order By: Relevance
“…Our data clearly showed that miR319-PvPCF5 pathway negatively regulated stem lignin content. Similar results were also reported in Arabidopsis [33]. However, we did not find differences in flowering time between WT and transgenic plants.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our data clearly showed that miR319-PvPCF5 pathway negatively regulated stem lignin content. Similar results were also reported in Arabidopsis [33]. However, we did not find differences in flowering time between WT and transgenic plants.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, PvPCF7 and PvPCF8 showed higher expression level in developed stems, and were negatively correlated with miR319 expression. Similarly, AtTCP4, a positive lignin content regulator, showed a similar expression pattern during Arabidopsis development [33]. However, the miR319 target PvPCF5/6/21 showed the opposite expression pattern with PvPCF7/8 during stem development.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…CIN‐TCPs also regulate differentiation of vasculature in the leaf. TCP4 directly activates VASCULAR‐RELATED NAC‐DOMAIN7 ( VND7 ) expression, leading to the differentiation of xylem vessel elements . VND7 belongs to the NAM/ATAF/CUC family of transcription factors and controls several downstream factors required for switching on genes involved in cellulose and lignin biosynthesis for secondary cell wall deposition critical for xylem differentiation and vessel formation .…”
Section: Cin‐tcps Control Cellular Expansion and Differentiationmentioning
confidence: 99%